My Trade: A Short History of British Journalism - Andrew Marr (London Pan Books, 2015)
How do you decide what is a 'story' and what isn't? What does a newspaper editor actually do all day? How do hacks get their scoops? How do the TV stations choose their news bulletins? How do you persuade people to say those awful, embarassing things? Who earns what? How do journalists manage to look in the mirror after the way they sometimes behave? The purpose of this insider's account is to provide an answer to all these questions and more. Andrew Marr's brilliant, and brilliantly funny, book is a guide to those of us who read newspapers, or who listen to and watch news bulletins but want to know more. Andrew Marr tells the story of modern journalism through his own experience. This is an extremely readable and utterly unique modern social history of British journalism, with all its odd glamour, smashed hopes and future possibility.
Keywords: Nonfiction; Journalism; History; Biography; Autobiography; Memoir; Politics; Writing; Global Citizenship (BIN1064-N)